Why do some women prefer submissive men? Hierarchically disparate couples reach higher reproductive success in European urban humans - Jozifkova, Eva; Konvicka, Martin; Flegr, Jaroslav (Neuro endocrinology letters, 2014)
OBJECTIVES: Equality between partners is considering a feature of the functional partnerships in westernized societies. However, the evolutionary consequences of how in-pair hierarchy influences reproduction are less known. Attraction of some high-ranking women towards low-ranking men represents a puzzle. METHODS: Young urban adults (120 men, 171 women) filled out a questionnaire focused on their sexual preference for higher or lower ranking partners, their future in-pair hierarchy, and hierarchy between their parents. RESULTS: Human pairs with a hierarchic disparity between partners conceive more offspring than pairs of equally-ranking individuals, who, in turn, conceive more offspring than pairs of two dominating partners. Importantly, the higher reproductive success of hierarchically disparate pairs holds, regardless of which sex, male or female, is the dominant one. In addition, the subjects preferring hierarchy disparity in partnerships were with greater probability sexually aroused by such disparity, suggesting that both the partnership preference and the triggers of sexual arousal may reflect a mating strategy. CONCLUSION: These results challenge the frequently held belief in within-pair equality as a trademark of functional partnerships. It rather appears that existence of some disparity improves within-pair cohesion, facilitating both cooperation between partners and improving the pairs' ability to face societal challenges. The parallel existence of submissivity-dominance hierarchies within human sexes allows for the parallel existence of alternative reproductive strategies, and may form a background for the diversity of mating systems observed in human societies. Arousal of overemphasized dominance/submissiveness may explain sadomasochistic sex, still little understood from the evolutionary psychology point of view.
Keywords: Choice Behavior; Reproduction; sexuální chování; Europe; sexuální partneři; mladiství; Evropa; průzkumy a dotazníky; mužské pohlaví; Masochism; mladý dospělý; Dominance-Subordination; Sexual Partners; Sadism; Young Adult; sadismus; městské obyvatelstvo; ženské pohlaví; Sexual Behavior; Humans; dominance a subordinace; Surveys and Questionnaires; rozmnožování; masochismus; Urban Population; výběrové chování; Female; Adolescent; lidé; Male